Doubt and dogmatism in Cicero’s Academica - Skvirsky, Alexandre (Revista Archai, 2019)
The objective is to show the peculiar way in which Cicero’s philosophical thinking is original and distances itself from the main representatives of the New Academy: the Roman thinker does not practice epoche, nor does he assign any special role to it in his thought. Instead, Cicero introduces the concept of doubt to characterize his own way of thinking.